Boron carbide-aluminum oxide pellet with two-stage pore structure and preparation method thereof
By using the sintering technology of γ-alumina, ɑ-alumina and boron carbide formed by hydrolysis of aluminum alkoxide, boron carbide with a double-stage pore structure, the problems of small pore size and large water absorption of existing materials were solved, and the effect of reducing water absorption and improving sintering activity was achieved.
Patent Information
- Application Number
- CN202411643123.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-25
AI Technical Summary
The pore size of the existing boron carbide-alumina pellets is small, resulting in large moisture adsorption, high sintering temperature, and difficult to effectively control the water absorption performance of the material, which increases the risk of breaking and training during the service cycle of the material.
Aluminum alkoxide hydrolysis is used to form γ-alumina with a macroporous structure as the second phase alumina raw material, and a boron carbide-alumina core pellet with a double-stage porous structure is prepared by sintering with the alumina raw material of the first phase of the alumina and the boron carbide powder.
It reduces the amount of water absorption in the air, improves sintering activity, inhibits boron volatility, and has high process compatibility, which is conducive to batch preparation. The materials can be used under medium and high temperature conditions.
Smart Images

Figure CN119683971A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of combustible poisons and neutron shielding materials for nuclear reactors, and in particular relates to a boron carbide-alumina core block with a double-level pore structure and a preparation method thereof. Background Art
[0002] Boron carbide-alumina composite materials, as burnable poisons, can extend the refueling cycle and improve the economic efficiency of the reactor unit by suppressing the excess reactivity during the initial loading or refueling of the reactor. Boron carbide-alumina uses boron with a large neutron absorption cross section as the nuclide that captures neutrons. After capturing neutrons, boron generates the stable nuclide lithium ( 7 Li) and Helium ( 4 He), the latter two are non-radioactive and have a very small neutron absorption cross section, so they have low residual reactivity when used as combustible poisons and shielding materials. Alumina has stable physical and chemical properties and is widely used in catalysts, adsorbents, ceramics, crystals and other fields. Nano-alumina (≤ average particle size 100nm) has unique applications in lithium battery separators, ceramic coatings, thermal conductivity and other fields.
[0003] Alumina has a very small neutron absorption cross section and a stable structure. High-density alumina ceramics can be used as thermal insulation and structural support elements in nuclear reactors. In the boron carbide-alumina core block, it is sintered with boron carbide at high temperature to form a porous composite ceramic (core block), and these pores are used to accommodate helium release. During the neutron irradiation cycle of 18-24 months or even longer, the boron carbide particles continue to decompose, while the interconnected alumina must still maintain the integrity of the core block structure and not pulverize and collapse. As a more advanced neutron absorption material solution, this boron carbide-alumina porous material is required to have extremely low water absorption in the air so that it can be assembled in the zirconium alloy cladding tube. Excessive adsorbed water vapor will cause hydrogen embrittlement damage to the zirconium alloy cladding. These requirements place high demands on the microstructure and component control of the material.
[0004] The preparation process of the boron carbide-alumina core block includes the selection of boron carbide and alumina powder for batching, mixing and other treatments, and the molding process can be extrusion, gel casting, dry pressing and the like. After the raw material components are fixed, the porosity of the boron carbide-alumina core block can be adjusted by changing the sintering temperature. Increasing the sintering temperature increases the density of the material and thus reduces the water absorption, but too high a sintering temperature will lead to an increase in the volatilization of boron in boron carbide, reduce the boron content in the boron carbide-alumina core block, and form boric acid that is easy to absorb water. However, too low a sintering temperature will reduce the density of the boron carbide-alumina material, that is, increase the porosity of the material, thereby increasing the water absorption capacity. Therefore, there are limitations in regulating and controlling the water absorption performance of the boron carbide-alumina material simply by adjusting the sintering temperature.
[0005] When the composition and porosity of the boron carbide-alumina pellets remain constant, the pore size distribution and pore structure are crucial for the adsorption and desorption of water molecules. However, conventional methods for adjusting the water absorption performance of boron carbide-alumina pellets often sacrifice the structural properties of the material, which may further increase the risk of breakage and forging during the service life of the material, and is not desirable. In addition, α-alumina is a stable phase of alumina at high temperatures, but due to its low sintering activity and the inhibition of boron carbide and free boron, volatile boron and carbon vapor, the densification efficiency is low. When the porosity of the boron carbide-alumina pellets is 30%, the pore size formed is generally below 1 micron. It can be seen that the pore size formed by the α-alumina raw materials used in the current technical level is small, the densification effect is poor, and the specific surface area inside the material is also increased, which is not conducive to reducing the water absorption capacity of the boron carbide-alumina material. Summary of the invention
[0006] In view of the shortcomings and defects of the existing boron carbide-alumina pellets, such as small pore size, large moisture adsorption, and high sintering temperature, the present invention proposes to use γ-alumina with a macroporous structure formed by hydrolysis of aluminum alkoxide as the second phase alumina raw material, and α-alumina first phase alumina raw material and boron carbide powder through sintering to prepare a boron carbide-alumina pellet with a double-stage pore structure (macroporous-mesoporous structure), which has the advantages of reducing water absorption in the air and having high sintering activity. The preparation method can inhibit and improve moisture absorption resistance, reduce sintering temperature and boron volatilization, and has high process compatibility and is conducive to batch preparation. The material obtained by the preparation method can be used as a combustible poison and neutron shielding material under medium and high temperature conditions.
[0007] In a first aspect, the present invention provides a boron carbide-alumina pellet with a dual-level pore structure, the boron carbide-alumina pellet with a dual-level pore structure comprising: boron carbide particles, and alumina coated on the surface of the boron carbide particles and having a macroporous structure and a mesoporous structure; Wherein: the pore size of the macroporous structure is 5-10 μm, preferably 6-8 μm; the pore size of the mesoporous structure is 0.1-2 μm, preferably 0.1-1 μm.
[0008] Preferably, the porosity of the boron carbide-alumina core block with a dual-level pore structure is 15-50%, preferably 20-40%.
[0009] Preferably, after the boron carbide-alumina core block with a dual-level pore structure absorbs water for 12-72 hours in an environment with a relative humidity of 80-85% and a temperature of 20-30° C., the hydrogen content is 15-30 ppm.
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned boron carbide-alumina pellet with a dual-level pore structure, the preparation method comprising the following steps: (1) Preparing γ-alumina with a macroporous structure; (2) preparing a slurry of a composite powder obtained by mixing the γ-alumina and α-alumina raw material powders with the boron carbide raw material powders, drying, granulating and forming the slurry to obtain a boron carbide-alumina blank; (3) Sintering the boron carbide-alumina blank to obtain the boron carbide-alumina core block having a dual-level pore structure.
[0011] Preferably, in step (1), aluminum alkoxide is hydrolyzed in a deionized water-organic solvent mixed solution, filtered, dried, and calcined to obtain the γ-alumina; Preferably, the mass ratio of the aluminum alkoxide to deionized water is 1:6-30, preferably 1:10-30, and the volume ratio of the organic solvent to deionized water is 1:2-20.
[0012] Preferably, the aluminum alkoxide is aluminum n-hexoxide or aluminum sec-butoxide; the organic solvent in the deionized water-organic solvent mixed solution is at least one of methanol, ethanol, toluene, xylene, isopropanol and butanol.
[0013] Preferably, the calcination temperature is 600-1000°C, and the calcination time is 1-8h, preferably 2-6h.
[0014] Preferably, in step (2), the D50 of the α-alumina raw material powder is 200-500 nm, and the D50 of the boron carbide raw material powder is 2-50 μm.
[0015] Preferably, in step (2), in the composite powder, the mass proportion of γ-alumina powder is 10-20%, the mass proportion of α-alumina raw material powder is 50-75%, and the mass proportion of boron carbide raw material powder is 15-30%.
[0016] Preferably, in step (3), the sintering is carried out in vacuum, nitrogen, argon or helium; the sintering temperature is 1300-1500° C., and the sintering time is 1-5 h.
[0017] Beneficial Effects (1) In the present invention, under the condition of a certain total porosity of the boron carbide-alumina pellet, the process of hydrolysis of aluminum alkoxide as a raw material is adopted to obtain high-porosity and high-activity γ-alumina as an alumina raw material, thereby forming a boron carbide-alumina pellet with a dual-level pore structure of macropores and mesopores, thereby reducing the moisture absorption capacity, avoiding hydrogen embrittlement damage, and avoiding defects such as harsh requirements on storage and use environment; (2) The dual-level pore structure boron carbide-alumina boron carbide-alumina material of the present invention uses γ-alumina particles obtained by hydrolysis of aluminum alkoxide as the source of alumina, without introducing new phases and impurities; (3) The γ-alumina obtained by the aluminum alkoxide hydrolysis method used in the present invention has uniformly distributed macropores, which prevents the small pores from adsorbing water vapor in the environment through capillary action and mesoporous alumina; (4) The method used in the present invention has mild reaction conditions and simple process, which is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A schematic diagram of a dual-level pore microstructure of a boron carbide-alumina pellet with a dual-level pore structure according to an example of the present invention; Figure 2 , 3 They are respectively microscopic schematic diagrams of the macropore and mesopore structure distribution of the pellets prepared in Example 2; Figure 4 The relationship between pore size and pore volume of the pellets prepared in Example 3 and the schematic diagram of the pore size distribution of the dual-stage pores; Figure 5 This is a SEM image of the pore structure distribution of the pellet prepared in Comparative Example 2; Reference numerals: 1. Boron carbide particles; 2. Particles derived from γ-alumina after sintering; 3. Particles derived from α-alumina raw material powder after sintering; 4. Macropores; 5. Mesopores. DETAILED DESCRIPTION
[0019] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0020] First, if Figure 1 As shown, the present invention provides a boron carbide-alumina pellet with a dual-level pore structure, wherein the boron carbide-alumina pellet with a dual-level pore structure comprises: boron carbide particles, and alumina coated on the surface of the boron carbide particles and having a macroporous structure and a mesoporous structure.
[0021] In some embodiments, the particle size of the boron carbide particles may be 5-40 μm.
[0022] In some embodiments, the pore size of the macroporous structure may be 5-10 μm, preferably 6-8 μm; the pore size of the mesoporous structure may be 0.1-2 μm, preferably 0.1-1 μm. By controlling the pore size of the macropores and mesopores within this range, the water absorption of the pellet can be reduced to 15-30 ppm. If the pore size is too small or the mesopore content is relatively high, the water absorption of the material will be enhanced, which may easily cause the risk of hydrogen embrittlement of the zirconium metal cladding.
[0023] In some embodiments, the porosity of the boron carbide-alumina pellet with a dual-level pore structure can be controlled to be 15-50%, preferably 20-40%.
[0024] The porosity of the pellets can be properly designed to ensure that the boron in the boron carbide absorbs neutrons in the reactor and generates helium bubbles (a 10 After the B atom absorbs the seed, it will become a 4 He and a 7 Li), the appropriate porosity needs to be controlled to accommodate helium bubbles and irradiation swelling. If the core porosity is too high, it will lead to excessive water absorption, causing hydrogen embrittlement and cladding damage, and too high porosity will lead to decreased mechanical properties and easily cause structural damage.
[0025] In some embodiments, after the boron carbide-alumina core block with a dual-level pore structure absorbs water for 12-72 hours at a relative humidity of 80-85% and a temperature of 20-30° C., the hydrogen content may be 15-30 ppm; and the compressive strength may reach 89 MPa.
[0026] The boron carbide-alumina composite structure with a dual-stage pore structure provided by the present invention can significantly improve the moisture absorption resistance of boron carbide-alumina when used as a discrete combustible poison, avoid hydrogen embrittlement of zirconium alloy cladding, simplify the drying and storage conditions before pipe loading, and reduce the use and storage costs of materials.
[0027] The following is an exemplary description of a method for preparing a boron carbide-alumina pellet having a dual-level pore structure provided by the present invention. The preparation method may include the following steps: (1) hydrolyzing aluminum alkoxide in a deionized water-organic solvent mixed solution, filtering, drying, and calcining to obtain γ-alumina with a pore size of 5-10 μm; (2) slurrying the composite powder obtained by mixing the γ-alumina and α-alumina raw material powders with the boron carbide raw material powders, drying, granulating and molding to obtain a boron carbide-alumina blank; (3) Sintering the boron carbide-alumina blank to form a dual-level pore structure to obtain the boron carbide-alumina core block having the dual-level pore structure.
[0028] In some embodiments, in step (1), the aluminum alkoxide may be aluminum hexoxide (Al(OC6H 13 )3) or aluminum sec-butoxide (A1(OC4H9)3); preferably, the mass ratio of the aluminum alkoxide to deionized water can be 1:6-30, preferably 1:10-30, and the volume ratio of the organic solvent to deionized water can be 1:2-20.
[0029] In some embodiments, in step (1), the organic solvent in the deionized water-organic solvent mixed solution can be at least one of methanol, ethanol, toluene, xylene, isopropanol, and butanol. The different polarities of water and organic solvent form a water-in-oil or oil-in-water structure to guide the structure of the pores during the hydrolysis process. Using only water will result in severe agglomeration.
[0030] In some embodiments, in step (1), the temperature for hydrolysis of the aluminum alkoxide may be 20-50° C., and the time for hydrolysis may be 2-24 h, preferably 2-6 h.
[0031] In some embodiments, in step (1), the drying temperature may be 100-300° C., and the drying time may be 12-24 hours.
[0032] In some embodiments, in step (1), the calcination temperature may be 600-1000° C., and the calcination time may be 1-8 h, preferably 2-6 h.
[0033] In step (1), the hydrolysis temperature, drying temperature and time, and calcination temperature and time all affect the pore size of γ-alumina. The hydrolysis temperature affects the hydrolysis rate, but if the temperature is too high, agglomerates are easily formed, and the porosity is reduced; the drying process is the process of removing water and further converting hydrolysis products such as AlOOH into alumina. If the calcination temperature is too high, the alumina will undergo phase transformation and agglomeration, which is not conducive to subsequent mixing and sintering.
[0034] In some embodiments, in step (2), the D50 of the α-alumina raw material powder may be 200-500 nm, and the D50 of the boron carbide raw material powder may be 2-50 μm. The micron-sized particle size of the boron carbide powder can ensure that less water is physically adsorbed, and the main water absorption source of the core is the surface of the alumina with finer grains and the pore surface of the composition.
[0035] In some embodiments, in step (2), in the composite powder, the mass proportion of γ-alumina powder can be 10-20%, the mass proportion of α-alumina raw material powder can be 50-75%, and the mass proportion of boron carbide raw material powder can be 15-30%. Among the three, boron carbide has the function of absorbing neutrons, and the proportion of boron carbide is designed according to the need for neutron absorption value during application; the rest is alumina, which serves as a matrix and provides a mechanical structure. By controlling the above mass proportions, the particles connected by alumina can maintain a complete structure without pulverization during the continuous consumption of boron carbide.
[0036] In some embodiments, in step (2), the drying temperature may be 120-300° C., preferably 150-250° C., and the drying time may be 12-24 h.
[0037] In some embodiments, in step (2), the molding method can be extrusion, casting or dry pressing; preferably, the dry pressing pressure can be 60-300 MPa, preferably 80-300 MPa, and more preferably 80-200 MPa.
[0038] In some embodiments, in step (3), the sintering can be carried out in vacuum, nitrogen, argon or helium; the sintering temperature can be 1300-1500°C, and the sintering time can be 1-5 hours. If the sintering temperature is too high or the sintering time is too long, it will cause severe sintering shrinkage and low porosity, which will not be able to accommodate the helium swelling after boron carbide absorbs neutrons, causing structural damage; if the sintering temperature is too low or the time is too short, it will result in low material densification, high porosity, and poor mechanical properties.
[0039] The present invention utilizes the hydrolysis of aluminum alkoxide to form hydrated aluminum hydroxide, and the organic solvent has a certain accelerating effect on the organic alcohol ester, thereby forming macroporous γ-crystalline aluminum oxide, and forming γ-alumina particles with rich pores through drying and calcination; after compounding with α-alumina with stable crystal form and smaller particles, due to sintering shrinkage and activity differences, a macroporous-mesoporous dual-level pore structure is finally formed, and micron-sized boron carbide is dispersed in the aluminum oxide particles. Compared with the pore structure formed by a single aluminum oxide raw material, the dual-level pores can also adjust the ratio of macropores to mesopores and the pore size distribution within a certain range.
[0040] Furthermore, the present invention creatively adjusts the ratio of macropores to mesopores by adjusting the raw materials of γ and α phase alumina. By matching the two alumina raw materials, a bipolar pore size distribution can be achieved to adjust the comparative area of the boron carbide-alumina core block. For example, when the porosity is limited to a certain value within the range of 15-50%, the specific surface area of the material is reduced by increasing the pore size, thereby reducing the active sites for water vapor adsorption, thereby achieving the purpose of reducing water absorption. In theory, the higher the porosity, the stronger the water absorption. When the porosity of the material is fixed, the water absorption brought by the large pore size distribution will be less than the water absorption caused by the medium pore size or small pore size. On the other hand, the small pore size also has the problem of significantly enhanced water absorption due to the capillary effect (surface tension).
[0041] Since α-alumina is a high-temperature stable phase, it has low sintering activity and limited powder volume shrinkage. Therefore, the pore size of the formed boron carbide-alumina pellet is small, and a higher sintering temperature is required to achieve densification. However, γ-alumina or precursor has high activity and unstable phase. It will eventually transform into α phase after sintering, and there is a larger volume shrinkage space during the sintering process. If the proportion of γ-alumina, the contributor of macropores, is too high, the density of the green billet will be low, the strength will be insufficient, and excessive sintering shrinkage will easily cause the boron carbide-alumina pellet to crack. The γ-alumina raw material hydrolyzed by aluminum alkoxide has large pores and voids, and has high activity. After mixing with α-alumina particles, at the same sintering temperature, the former shrinks and leaves larger pores, while the latter forms medium pores after sintering due to its small pores and high bulk density.
[0042] It is also necessary to point out that the dual-stage pore distribution to adjust the water absorption requires creative design based on the physical and chemical causes of the water absorption of the boron carbide-alumina core block, the properties of alumina, the interface reaction of alumina and boron carbide, the sintering mechanism of the composite ceramic, and how to form reasonable pores and surface areas without introducing additional impurities or impurities. Among them, it is particularly important to consider that the boron carbide (B4C) particles are not a stoichiometric compound, and their surface generally contains 0.5wt% water-soluble boron, nitric acid-soluble boron, etc., as well as iron impurities, and after the high-temperature sintering process, boric anhydride, boric acid, iron oxide, and aluminum boron oxide compounds are formed, all of which may cause water absorption.
[0043] The boron carbide-alumina core block with a double-stage pore structure provided by the present invention can be used as discrete combustible poisons for reactors and as shielding materials under medium and high temperature conditions.
[0044] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0045] Example 1
[0046] The method for preparing the boron carbide-alumina pellet with a dual-level pore structure provided in this embodiment comprises the following steps: (1) After 50 mL of methanol and 200 mL of water were stirred and mixed, 10 g of aluminum n-hexoxide was slowly added, the mixture was stirred evenly, and the mixture was allowed to stand for 24 hours; the suspension was filtered to obtain hydrated aluminum hydroxide (precursor of γ-alumina), the precursor was dried at 150° C. for 12 hours, and calcined at 600° C. for 2 hours to obtain γ-alumina; (2) The γ-alumina obtained in step (1) is used as the second phase of the alumina raw material, the mass proportion of the mixed powder is 10%, and the α-alumina with a D50 of 200 nm is used as the first phase of the alumina raw material, accounting for 75% by mass, and the boron carbide powder (D50 is 30 μm) with a mass proportion of 15% is uniformly mixed with deionized water and a binder, and then spray granulated, and dried at 200° C. to obtain a ceramic powder; isostatic pressing is performed at a pressure of 120 MPa to obtain a boron carbide-alumina blank; (3) Sintering the boron carbide-alumina blank obtained in step (2) at 1350° C. for 2 h in an argon atmosphere to obtain a boron carbide-alumina core block having a dual-level pore structure.
[0047] The test shows that the compressive strength of the core block is 89MPa. To facilitate performance comparison, the core block is first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) is then tested using a nitrogen-oxygen-hydrogen meter and found to be 21ppm.
[0048] Example 2
[0049] The preparation method of the boron carbide-alumina pellet with a dual-level pore structure provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the aluminum alkoxide is aluminum sec-butoxide, and the precursor is dried at 120° C.; In step (2), the mass ratio of γ-alumina is 15%, and the mass ratio of α-alumina with a D50 of 300 nm is 70%.
[0050] To facilitate performance comparison, the pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) was then tested using a nitrogen, oxygen and hydrogen meter and found to be 20 ppm.
[0051] Figure 2 , 3 They are respectively microscopic schematic diagrams of the macropore and mesopore structure distribution of the core blocks prepared in Example 2.
[0052] Example 3
[0053] The preparation method of the boron carbide-alumina pellet with a dual-level pore structure provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the amount of deionized water is 100 mL, the amount of aluminum alkoxide is 5 g of aluminum sec-butoxide, the precursor is dried at 120° C., and the calcination temperature is 1000° C.; In step (2), the mass ratio of γ-alumina is 15%, and the mass ratio of α-alumina with a D50 of 300 nm is 70%; In step (3), the sintering temperature is 1400°C.
[0054] To facilitate performance comparison, the pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) was then tested using a nitrogen, oxygen and hydrogen meter and found to be 19 ppm.
[0055] Figure 4 The pore size-pore volume relationship and the schematic diagram of the pore size distribution of the double-stage pores of the core block prepared in Example 3. As can be seen from the figure, the two most probable pore size peaks of the pore size distribution correspond to the mesopores of 300 nm and the macropores of 7 μm, and there are also a small number of micropores of several nanometers.
[0056] Example 4
[0057] The preparation method of the boron carbide-alumina pellet with a dual-level pore structure provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the organic solvent is 10 mL of isopropanol, the deionized water is 100 mL, the aluminum alkoxide is 5 g of aluminum sec-butoxide, the precursor is aged for 12 hours, the precursor is dried at 120° C. for 24 hours, and the calcination temperature is 800° C.; In step (2), the mass ratio of γ-alumina is 15%, the mass ratio of α-alumina with a D50 of 300 nm is 70%, and the D50 of the boron carbide powder is 20 μm; In step (3), the sintering temperature is 1500°C.
[0058] To facilitate performance comparison, the pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) was then tested using a nitrogen, oxygen and hydrogen meter and found to be 21 ppm.
[0059] Example 5
[0060] The preparation method of the boron carbide-alumina pellet with a dual-level pore structure provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the organic solvent is 10 mL of butanol, the deionized water is 100 mL, the aluminum alkoxide is aluminum sec-butoxide, the precursor is dried at 120° C. for 24 h, and the calcination temperature is 800° C.; In step (2), the mass ratio of γ-alumina is 15%, the mass ratio of α-alumina with a D50 of 300 nm is 70%, the D50 of the boron carbide powder is 20 μm, the drying temperature is 250° C., and the dry pressing pressure is 150 MPa; In step (3), the sintering temperature is 1500°C.
[0061] To facilitate performance comparison, the pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) was then tested using a nitrogen, oxygen and hydrogen meter and found to be 22 ppm.
[0062] Example 6
[0063] The preparation method of the boron carbide-alumina pellet with a dual-level pore structure provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the organic solvent is 10 mL of butanol and the deionized water is 100 mL. The precursor is dried at 120° C. for 24 h and the calcination temperature is 800° C.; In step (2), the mass ratio of γ-alumina is 20%, the mass ratio of α-alumina with a D50 of 300 nm is 60%, the D50 of boron carbide powder is 20 μm, the mass ratio is 20%, and the dry pressing pressure is 250 MPa; In step (3), the sintering temperature is 1400°C.
[0064] To facilitate performance comparison, the pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) was then tested using a nitrogen, oxygen and hydrogen meter and found to be 18 ppm.
[0065] Example 7
[0066] The preparation method of the boron carbide-alumina pellet with a dual-level pore structure provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the organic solvent is 10 mL of butanol, the deionized water is 100 mL, the aluminum n-hexoxide is 15 g, the precursor is dried at 120° C. for 24 h, and the calcination temperature is 800° C.; In step (2), the mass ratio of γ-alumina is 15%, the mass ratio of α-alumina with a D50 of 500 nm is 55%, the mass ratio of boron carbide powder is 30%, and the dry pressing pressure is 200 MPa; In step (3), the sintering temperature is 1480°C.
[0067] To facilitate performance comparison, the pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) was then tested using a nitrogen, oxygen and hydrogen meter and found to be 26 ppm.
[0068] Comparative Example 1
[0069] The preparation method of the boron carbide-alumina pellet provided in this comparative example refers to that in Example 1, the main difference is that: step (1) is not performed, and the alumina raw material is directly α-alumina with a D50 of 200 nm; and sintering aid SiO2 or MgSiO3 is used.
[0070] The pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C to absorb water for 48 hours, and then the hydrogen content (as an indicator of water absorption) was tested with a nitrogen-oxygen-hydrogen meter and found to be 38 ppm.
[0071] Comparative Example 2
[0072] The preparation method of the boron carbide-alumina pellet provided in this comparative example comprises the following steps: (1) conventional γ-alumina powder is used as the second phase of alumina raw material, the mass ratio of the mixed powder is 15%, α-alumina with a D50 of 200 nm is used as the first phase of alumina raw material, the mass ratio is 70%, and 15% of boron carbide powder (D50 is 30 μm) is uniformly mixed with deionized water and a binder, and then spray granulated, and dried at 200° C. to obtain ceramic powder; isostatic pressing is performed at a pressure of 120 MPa to obtain a boron carbide-alumina blank; (2) Sintering the boron carbide-alumina blank obtained in step (1) at 1350° C. in an argon atmosphere to obtain a boron carbide-alumina pellet.
[0073] Figure 5 This is a SEM image of the pore structure distribution of the pellet prepared in Comparative Example 2. The arrows in the figure indicate some micron-sized boron carbide particles, and the rest are alumina phases. It can be seen that there are 0.1-1 μm pores between the alumina particles, and no macropores larger than 1 μm are included.
[0074] To facilitate performance comparison, the pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) was then tested using a nitrogen, oxygen and hydrogen meter and found to be 42 ppm.
[0075] Comparative Example 3
[0076] The preparation method of the boron carbide-alumina pellet provided in this comparative example refers to Example 1, with the main differences being: In step (2), the mass ratio of γ-alumina as the second phase of the alumina raw material in the mixed powder is 5%, and the mass ratio of α-alumina with a D50 of 200 nm as the first phase of the alumina raw material is 80%.
[0077] The pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C to absorb water for 48 hours, and then the hydrogen content (as an indicator of water absorption) was tested by a nitrogen-oxygen-hydrogen meter and found to be 43 ppm.
[0078] Comparative Example 4
[0079] The preparation method of the boron carbide-alumina pellet provided in this comparative example refers to Example 1, with the main differences being: In step (2), the mass ratio of γ-alumina as the second phase of the alumina raw material in the mixed powder is 30%, and the mass ratio of α-alumina with a D50 of 200 nm as the first phase of the alumina raw material is 55%.
[0080] The core block was first placed in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours to absorb water. The hydrogen content (as an indicator of water absorption) was tested by a nitrogen-oxygen-hydrogen meter and found to be 19 ppm. However, the compressive strength was reduced to 55 MPa after testing.
[0081] Comparative Example 5
[0082] The preparation method of the boron carbide-alumina pellet provided in this comparative example refers to that in Example 1, the main difference is that; In step (3), the sintering temperature is 1200°C.
[0083] The pellets were first placed in an oven at a relative humidity of 80% and a temperature of 25°C to absorb water for 48 hours, and then the hydrogen content (as an indicator of water absorption) was tested with a nitrogen-oxygen-hydrogen meter and found to be 55 ppm.
[0084] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A boron carbide-alumina pellet with a dual-stage pore structure, characterized in that: The boron carbide-alumina core block with a dual-level pore structure comprises: boron carbide particles, and alumina coated on the surface of the boron carbide particles and having a macroporous structure and a mesoporous structure; Wherein: the pore size of the macroporous structure is 5-10 μm, preferably 6-8 μm; the pore size of the mesoporous structure is 0.1-2 μm, preferably 0.1-1 μm.
2. The boron carbide-alumina pellet with a dual-level pore structure according to claim 1, characterized in that: The porosity of the boron carbide-alumina core block with a dual-level pore structure is 15-50%, preferably 20-40%.
3. The boron carbide-alumina pellet with a dual-level pore structure according to claim 1 or 2, characterized in that: After the boron carbide-alumina core block with a dual-level pore structure absorbs water for 12-72 hours under an environment of relative humidity of 80-85% and temperature of 20-30° C., the hydrogen content is 15-30 ppm.
4. A method for preparing a boron carbide-alumina pellet with a dual-level pore structure according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Preparing γ-alumina with a macroporous structure; (2) slurrying the composite powder obtained by mixing the γ-alumina and α-alumina raw material powders with the boron carbide raw material powders, drying, granulating and molding to obtain a boron carbide-alumina blank; (3) Sintering the boron carbide-alumina blank to obtain the boron carbide-alumina core block having a dual-level pore structure.
5. The preparation method according to claim 4, characterized in that: In step (1), aluminum alkoxide is hydrolyzed in a deionized water-organic solvent mixed solution, filtered, dried, and calcined to obtain the γ-alumina; Preferably, the mass ratio of the aluminum alkoxide to deionized water is 1:6-30, preferably 1:10-30, and the volume ratio of the organic solvent to deionized water is 1:2-20.
6. The preparation method according to claim 4 or 5, characterized in that: The aluminum alkoxide is aluminum n-hexoxide or aluminum sec-butoxide; the organic solvent in the deionized water-organic solvent mixed solution is at least one of methanol, ethanol, toluene, xylene, isopropanol and butanol.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The calcination temperature is 600-1000° C., and the calcination time is 1-8 hours, preferably 2-6 hours.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (2), the D50 of the α-alumina raw material powder is 200-500nm, and the D50 of the boron carbide raw material powder is 2-50μm.
9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (2), in the composite powder, the mass proportion of γ-alumina powder is 10-20%, the mass proportion of α-alumina raw material powder is 50-75%, and the mass proportion of boron carbide raw material powder is 15-30%.
10. The preparation method according to any one of claims 4 to 9, characterized in that: In step (3), the sintering is carried out in vacuum, nitrogen, argon or helium; the sintering temperature is 1300-1500° C., and the sintering time is 1-5 hours.